ANALISIS KETERAMPILAN BERBICARA PADA MATA PELAJARAN BAHASA INDONESIA KELAS XI AGRIBISNIS TANAMAN PANGAN DAN HORTIKULTURA SMKN 1 PAKUAN RATU - Purnami, Ni Made Ayu; Santi, Ketut; Janawati , Desak Putu Anom (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2025)
Speaking skills influence someone in conveying messages in speaking or communicating activities. Not all students are able to speak Indonesian, because sometimes students are still carried away by their respective regional languages. Regional languages ​​are very attached so that students have difficulty explaining using Indonesian, therefore students find it easier to explain using their regional languages. This study seeks to identify the process of analyzing Indonesian speaking skills of class XI agribusiness food crops and horticulture (ATPH) at SMK N 1 Pakuan Ratu. A qualitative descriptive research design was used in this study. The research findings indicate that the majority of XI ATPH students at SMK N 1 Pakuan Ratu are interested in learning Indonesian, but are constrained by the habit of using regional languages ​​in communication. The results show that the motivation and interest of XI ATPH students of SMK N 1 Pakuan Ratu in learning Indonesian are quite high, this is reflected in every learning meeting, these students are very enthusiastic in learning Indonesian language skills. However, students' Indonesian speaking skills do not develop optimally due to environmental factors, habits, and parenting patterns. These students only learn Indonesian when they are in the school environment, while returning to using regional languages ​​in the family or community environment, thus the role of teachers is very crucial in teaching Indonesian, which is expected to enable students to start getting used to communicating in Indonesian outside the school environment.